O USO DE DESIGN STRUCTURE MATRIX PARA IDENTIFICAÇÃO DE ASPECTOS CRÍTICOS INERENTES À ADOÇÃO DE TECNOLOGIA CONSTRUTIVA - Sato, Luana; Barros, Mercia; Gonçalves Jr, Marco; Ceotto, Luiz; Junginger, Max; John, Vanderley (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The insertion of a constructive technology innovation in the production of buildings, without due systemic analysis, can generate liabilities that may jeopardize its future consolidation in the market. As the building is a complex system, the systemic assessment of its behavior in use is essential. Other industries such as aerospace, which also work with complex products, adopt as a tool of analysis the Design Structure Matrix (DSM), aiming the subdivision of complex problems into smaller and easier to solve ones. The objective of this work is to verify the feasibility of using the DSM tool for analysis of innovative construction technologies. A literature review was made for fully understand the tool, which was applied in a case study involving Light Steel Framing, taking as parameter of analysis the Performance Standard (ABNT NBR15575: 2013). The result obtained confirm that the DSM induces a systemic look at all the interactions generated by the new technology in the constructive context of the building and, by this, allows a broader and deeper analysis of the consequences of adopting the new technology. It can also be concluded that its efficiency in evaluating complex problems depends on the maturity of the team performing it.